UTILIZATION OF FINE BRAN WATER FERMENTATION EXTRACT WITH DIFFERENT DOSES AGAINST POPULATION OF SILK WORMS (Tubifex sp): PEMANFAATAN EKSTRAK FERMENTASI AIR DEDAK HALUS DENGAN DOSIS YANG BERBEDA TERHADAP POPULASI CACING SUTRA (Tubifex sp - Humeira; Kurnia; Nurhatijah; Indah Permata Sari; Ika Rezvani Aprita; Zulvia Maika Letis; Nurviana (PT. ROCE WISDOM ACEH, 2025)
The purpose of this study was to determine the effect of fermented bran extract with different doses on the biomass growth of Silkworms (Tubifex sp). This research was conducted in August 2021 at the Laboratory of the Fish Seed and Feed Production Technology Study Program, Politeknik Indonesia Venezuela. The design used was a non-factorial completely randomized design consisting of 4 treatments and 4 replicates. The highest biomass of silkworms (Tubifex sp) was obtained in treatment A (without the addition of fine bran fermentation extract) with an average biomass of 32.5 grams, while the best absolute length growth of silkworms was obtained in treatment D (Addition of 200 ml fine bran fermentation extract) with a length value of 2.5 cm. The results of the analysis of variance showed that the addition of fermented bran extract had a significant effect (P>0.05) on biomass and absolute length growth of silkworms (Tubifex sp). Water quality results showed pH ranged from 8.4 - 10.4 and water temperature ranged from 26.9-270C.